2000
DOI: 10.1034/j.1600-051x.2000.027007489.x
|View full text |Cite
|
Sign up to set email alerts
|

Fcα receptor I (CD89) on neutrophils in periodontal lesions

Abstract: It is suggested that FcalphaRI on neutrophils may play an important rôle in elimination of IgA-opsonized bacteria, both in periodontal tissue and the adjacent pockets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Our results revealed that CD68 + intestinal lamina propria macrophages failed to express CD89. These results are in agreement with previous observations that intestinal and gingival macrophages lack CD89 [34, 35]. Interestingly, macrophages isolated from the peritoneal cavity and bronchoalveolar lavage still expressed detectable levels of CD89 (and CD14), suggesting that these cells are less mature than those found in intestinal lamina propria or gingiva, perhaps owing to the lack of a tissue‐specific factor responsible for promoting terminal differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed that CD68 + intestinal lamina propria macrophages failed to express CD89. These results are in agreement with previous observations that intestinal and gingival macrophages lack CD89 [34, 35]. Interestingly, macrophages isolated from the peritoneal cavity and bronchoalveolar lavage still expressed detectable levels of CD89 (and CD14), suggesting that these cells are less mature than those found in intestinal lamina propria or gingiva, perhaps owing to the lack of a tissue‐specific factor responsible for promoting terminal differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…GCF PMN were found to exhibit higher levels of Fc␣RI and Fc␣RI-positive cells than PB PMN. These findings were in accordance with the results of immunohistochemical work showing that periodontal pocket areas were heavily infiltrated with Fc␣RI-expressing neutrophils (62). Fc␣RI expression on human PMN has been shown to be up-regulated by interleukin 8 (IL-8) (41), tumor necrosis factor alpha (TNF-␣) (26), and FMLP (25).…”
Section: Discussionsupporting
confidence: 85%
“…Consistently, mucosal phagocytes have been shown to exhibit an increased capacity to bind and ingest IgA-opsonized targets (14,25). Indeed, GCF PMN are immunocompetent cells that move from the bloodstream to mucosal sites (periodontal pocket), where subgingival plaque bacteria are coated with IgA (62). Fc␣R is expressed exclusively on phagocytes, whereas Fc␥R is more widely expressed on leukocytes (39).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, periodontal lesions were shown to contain significant levels of IgA and IgG antibody‐secreting cells (8). Moreover, dense infiltrates of PMNs with high expression levels of IgA and IgG Fc receptors (FcαR and FcγR) have been detected in the disease periodontium (9). FcαR or FcγR on PMNs may thus play a role in the pathogenesis of periodontitis.…”
Section: Distribution Of Immunoglobulin a Fc Receptor (Fcαri) Nt 324 mentioning
confidence: 99%
“…FcαRI expression levels on human PMNs have been shown to be upregulated by interleukin‐8 (27) and tumor necrosis factor‐α (28), both of which can be detected in inflamed gingival tissue of periodontitis patients (29, 30). Additionally, an immunohistochemical study documented periodontal pocket areas to be heavily infiltrated with FcαRI‐expressing neutrophils (9). Significant IgA levels specific to periodontal pathogens were observed in GCF and gingival tissue of periodontitis patients (6, 8).…”
Section: Distribution Of Immunoglobulin a Fc Receptor (Fcαri) Nt 324 mentioning
confidence: 99%